(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
Simulated rain trials were conducted with the primary objective of determining the influence of nutrient management on surface runoff quality from the grazed fescue pastures. The nutrient management treatments included no add fertilizer or broiler (C), soil applied inorganic fertilizer (AIF), soil applied broiler litter (ABL) and broiler litter fed to steers (FBL). Runoff from simulated rainfall events was analyzed for dissolved inorganic P (DPi), molybdate reactive P (MRP), total dissolved P (TDP), particulate P (PP), total P (TP), and fecal coliform (FC) counts. Concentrations of DPi, MRP, and TDP in surface runoff, while decreasing with time, were higher in AIF, ABL, and FBL than in the control (C). Particulate P losses were lower than the MRP fraction, constituting 27, 42, and 27 % for AIF, ABL, and FBL, respectively, compared to 50% in the C treatment. Counts of FC were higher than 7000 CFU 100 mL-1 in all treatments and constitute source of pollution. P concentrations in the soil, as determined by Mehlich-1, increased from 18 mg kg-1 in the soil at the start of the experiment in 1995 to 27, 205, 213, and 96 mg kg-1 in the top 0-5 cm soil depth in 2001 for C, AIF, ABL, and FBL treatments, respectively. These P concentrations were reflected in the concentrations of P in surface runoff and suggest that intensive nutrient managements of grazed pasture increase the risk of P pollution of ground and surface waters. تهدف الدراسة إلى تقصي تأثير نظام إدارة خصوبة المراعي على نوعية مياه السيل السطحي، حيث تضمنت معاملة الشاهد التي لم تتلق إضافة سمادية ( C )، معاملة تلقت تسميداً معدنياً (AIF)، معاملة تلقت إضافة من فضلات مزارع الدواجن (ABL)، معاملة تمت تغذية العجول بفضلات الدواجن (FBL). تم إجراء عاصفة مطرية صنعية بشدة 65-72 ملم/ساعة وتم تتبع كمية ماء السيل السطحي كل 5 دقائق ولمدة 30 دقيقة. قدر في ماء السيل السطحي كل من الفوسفور الذائب بصوره: المعدني (Dpi)، المتفاعل مع الموليبدنيوم (MRP)، الكلي (TDP)؛ والفوسفور المرتبط بالجسيمات الغروية (PP) والكلي (TP)، وكذلك تم تقدير تعداد بكتريا الكوليفورم البرازية (FC). كما وتم تقدير الفوسفور المتاح بطرق مختلفة ودرست علاقات الارتباط مع كل من الفوسفور الذائب المعدني والمتفاعل مع الموليبدات و الكلي في ماء السيل السطحي. في الوقت الذي تتناقص فيه تراكيز الفوسفور الذائب بأشكاله المختلفة Dpi, MRP, TDP في ماء السيل السطحي مع مرور زمن تشكل السيل السطحي فقد كانت أعلى في المعاملات مقارنة بالشاهد. أما بالنسبة لتراكيز الفوسفور المرتبط بالجسيمات الغروية PP فقد كان أعلى في معاملات التسميد أيضاً إلا أنه شكل 50% من الفوسفور الكلي في ماء السيل السطحي في معاملة الشاهد مقارنة بالنسب 27، 42، و 27% في المعاملات FBL, ABL, AIF على التوالي. كما سجلت بكتريا الكوليفورم معدلات عالية جداً في جميع المعاملات يزيد عن 7000 وحدة بكتيرية/100 سم3. لقد أوضحت دراسة اختبار الفوسفور المتاح في التربة (Mehlich-1) أن هنالك تراكم للفوسفور نتيجة نظام الإضافة السمادية على مدار سبع سنوات من 18 مغ/كغ إلى 27 و 205 و 213 و 96 مغ/كغ في المعاملات FBL, ABL, AIF, C على التوالي, وكان لها علاقة ارتباط وثيقة مع تراكيز الأشكال المختلفة للفوسفور الذائب في ماء السيل السطحي.